Dose enhancement and cytotoxicity of gold nanoparticles in colon cancer cells when irradiated with kilo‐ and mega‐voltage radiation. Issue 1 (27th May 2016) - Hau, Herman; Khanal, Dipesh; Rogers, Linda; Suchowerska, Natalka; Kumar, Rajiv; Sridhar, Srinivas; McKenzie, David; Chrzanowski, Wojciech
Abstract: Despite major advances in the field of radiotherapy, healthy tissue damage continues to constrain the dose that can be prescribed in cancer therapy. Gold nanoparticles (GNPs) have been proposed as a solution to minimize radiation‐associated toxicities by enhancing the radiation dose delivered locally to tumor cells. In the current study, we investigated the application of third‐generation GNPs in two‐dimensional (2D) and three‐dimensional (3D) cell cultures and whether there is synergy between the nanoparticles and kilo‐ or mega‐voltage radiation to cause augmented cytotoxicity. The 10‐nm GNPs were found to be nontoxic in both 2D and 3D in vitro cultures of colon cancer cells at concentrations of up to 10–25 µg/ml. There was a significant increase in cell survival fraction reduction following exposure to 1 Gy of kilo‐voltage (18.3%) and 2 Gy of mega‐voltage (35.3%) radiation when the cells were incubated with 50 µg/ml of GNPs. The biocompatibility of the GNPs combined with their substantial synergy with radiation encourages further investigations into their application in targeted cancer treatment.